2014
DOI: 10.1002/bmc.3290
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of oleanolic acid, ursolic acid, quercetin and apigenin in Swertia mussotii Franch by capillary zone electrophoresis with running buffer modifier

Abstract: The method of capillary zone electrophoresis (CZE) with direct UV detection was developed for the determination of oleanolic acid, ursolic acid, quercetin and apigenin. and then for the first time successfully applied to the analysis of four analytes in Swertia mussotii Franch and its preparations. Various factors affecting the CZE procedure were investigated and optimized, and the optimal conditions were: 50 × 10(-3) mol/L borate-phosphate buffer (pH 9.5) with 5.0 × 10(-3) mol/L β-cyclodextrin, 15 kV separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Gao et al. developed capillary zone electrophoresis (CZE) with direct UV detector for the determination of oleanolic acid, ursolic acid, quercetin and apigenin in Swertia mussotii Franch . This method is considered to be accurate method for simultaneous determination of oleanolic acid, ursolic acid, quercetin and apigenin in this plant.…”
Section: Application and Advances Ce Analysis Of Plants Flavonoidsmentioning
confidence: 99%
“…Gao et al. developed capillary zone electrophoresis (CZE) with direct UV detector for the determination of oleanolic acid, ursolic acid, quercetin and apigenin in Swertia mussotii Franch . This method is considered to be accurate method for simultaneous determination of oleanolic acid, ursolic acid, quercetin and apigenin in this plant.…”
Section: Application and Advances Ce Analysis Of Plants Flavonoidsmentioning
confidence: 99%
“…The PTAs in FF was extracted by the organic solvent and finally transferred into the BGE for CE analysis. The extraction procedure was referred to the previous studies . Briefly, the fruits were powdered, homogenized, and dried 6 hours in the oven at 50°C.…”
Section: Methodsmentioning
confidence: 99%
“…Certain types of PTAs in some Chinese herbs, such as Prunella vulgaris L . , Swerita mussotii and Pterocephalus hookeri , could be detected by capillary zone electrophoresis (CZE) or micellar electrokinetic chromatography (MEKC) . Otherwise, Chen's group also reported that three bioactive triterpenes were simultaneously separated by nonaqueous capillary electrophoresis (NACE) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several methods have been developed for the determination of UA, including micellar electrokinetic capillary chromatography (Zhang et al, 2005), HPLC (Li et al, 2019), LC-MS (Novotny et al, 2003), capillary zone electrophoresis (Gao et al, 2015b) and UV spectroscopy (Pironi et al, 2018). These methods all require complicated sample preparation procedures and a sophisticated operation.…”
Section: Introductionmentioning
confidence: 99%